Detection of EGFR and KRAS mutations on trans-thoracic needle aspiration of lung nodules by high resolution melting analysis. Issue 12 (28th July 2009) - Fassina, A; Gazziero, A; Zardo, D; Corradin, M; Aldighieri, E; Rossi, G P
Abstract : Background: EGFR and KRAS are the target genes for tumour response to epidermal growth factor receptor (EGFR) inhibitors. Aims: To investigate EGFR and KRAS mutational status with high resolution melting (HRM) analysis applied to cytological material obtained from trans-thoracic needle aspiration (TTNA) in order to better select patients for targeted therapy. Methods: DNA was extracted from fixed material of 108 TTNAs under CT guidance, from 108 consecutive patients. In 77 TTNAs (71.3.%) that were positive for non-small cell lung cancer, the variant in exon 21 (the missense mutation at codon 858, L858R) and the deletion in exon 19 (in frame deletion at codons 747–749) of the EGFR gene, and the point mutation in exon 2 of KRAS were investigated with HRM assay using sequencing as the reference "gold standard". Results: Nine (11.7%) samples were positive for KRAS exon 2 mutations, and two (2.6%) samples were positive for the EGFR exon 21 missense mutation by HRM assay. No deletion at exon 19 for EGFR was detected by HRM analysis. All HRM results were confirmed by direct DNA sequencing. Conclusions: HRM analysis of cytological material was accurate for the detection of two major EGFR mutations and KRAS mutations in exon 2. HRM analysis was fast, easy to apply, cheap, highly reproducible, and could be used with small amounts of material, such as is obtainable with needle lavage. Therefore, it may be useful as an adjunct to the cytological report that yields valuable molecular information.